2021
DOI: 10.3390/ijms22041911
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Deletion of a SVA Retrotransposon Demonstrates Function as a cis-Regulatory Element at the TRPV1/TRPV3 Intergenic Region

Abstract: SINE-VNTR-Alu (SVA) retrotransposons are a subclass of transposable elements (TEs) that exist only in primate genomes. TE insertions can be co-opted as cis-regulatory elements (CREs); however, the regulatory potential of SVAs has predominantly been demonstrated using bioinformatic approaches and reporter gene assays. The objective of this study was to demonstrate SVA cis-regulatory activity by CRISPR (clustered regularly interspaced short palindromic repeats) deletion and subsequent measurement of direct effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Additionally, these two variables appear to be correlated. This study supports a growing body of evidence that SVA RIPs can influence expression of nearby genes 28 , 29 , and should therefore be regarded as potentially important regulatory inputs for local gene expression.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, these two variables appear to be correlated. This study supports a growing body of evidence that SVA RIPs can influence expression of nearby genes 28 , 29 , and should therefore be regarded as potentially important regulatory inputs for local gene expression.…”
Section: Discussionsupporting
confidence: 85%
“…Price et al identified that the trpv1/trpv3 intergenic region is enriched with humanspecific SINE-VNTR-Alu (SVA) retrotransposon insertions [20]. The SVA, located approximately 400 bp downstream the trpv1 3 UTR and 5.7 kb upstream of the 5 trpv3 transcriptional start site, serves as a cis-regulatory element for the trpv3 gene.…”
Section: Gene and Evolutionmentioning
confidence: 99%
“…TRPV3 is expressed in sensory neurons such as the dorsal root ganglia (DRG) and in the trigeminal ganglia (TG) in humans and nonhuman primates [8]. In many human tissues, TRPV1, functionally significant in neuropathic pain conditions, and TRPV3, are co-expressed and can form heteromeric channels, which was not observed in mice [20]. Perhaps this underlies the key regulatory differences between the two species.…”
Section: Painmentioning
confidence: 99%
“…For a long time, CRISPR-based large fragment deletions have been used to study CREs in various cells . Using two sgRNAs to target a sequence causes the sequence between the two sgRNAs to be deleted. Currently, CRISPR/Cas-based large fragment deletion in animals is used to study lncRNAs and CREs. The improvement and application of this tool improved molecular breeding methods and broadened the application range of CRISPR toolsets (Supplementary Table 1).…”
Section: Dissection Of Plant Genes’ Function By Crispr Toolsetsmentioning
confidence: 99%